Implementation of hybrid encryption method using caesar cipher algorithm - Tat Wi, Charomie (2010)
In daily life, we use internet or accessing information from various sources. Some of the procedure requires us to sending our own information. The objective of this project is to explore the way of doing encryption, improve certain aspect of the existing algorithm and to find out a way to create better security. In this project, encryption will be implemented in information on a web that makes it hard to be readable and secure. For that matter, encryption method known as Caesar cipher, one of the simplest and most widely used encryption techniques. In this encryption, it uses the substitution cipher in which each letter in the plaintext is replaced by some fixed number of position down the alphabet. This method is names after Julius Caesar who using this method to communicate with his generals. The result from this project is a data which is encrypted and be decrypted to its readable form. As a conclusion, Caesar cipher algorithm can be implemented in hybrid encryption project to make data secure and better.